Sentience of the Earth: Eco-Buddhist Mandalizing of Dwelling Place in Amdo, Tibet - Yu, Dan (Journal for the study of religion, nature and culture, 2014)
I present a case study of Tibetan Buddhism as a lived religion embodied in the greater environment of a village in eastern Amdo, Tibet. Speci?cally, I explore the interconnectedness of place-based Buddhist practices that, I argue, present an example of care for sacred landscapes in Tibetan Buddhism. Based on my ethnographic work, I make a threefold argument. First, Buddhism in Tibet can be viewed as ‘an emplaced religion’ signifying the antecedent role of place in forging the complex intertwinement of the Earth and humans. Second, the sacredness in the local landscape entails a shared, hierarchical entwinement of place, humans, and gods. Third, the way the villagers, especially the lay tantric yogis, consecrate their environment expresses their connection and care for the landscape.